1995
DOI: 10.1111/j.1530-0277.1995.tb00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Striatal Adenosine in the Modulation of Acute Ethanol‐Induced Motor Incoordination in Rats

Abstract: Several reports from our laboratory have suggested the involvement of the brain adenosinergic system in ethanol-induced motor incoordination (EIMI). This study is an extension of the previous work and pertains to the evaluation of the role of the striatal adenosine in EIMI in male Sprague-Dawley rats. Using the motor incoordination induced by 1.5 g/kg of ethanol (ip) as a test response, the possible behavioral interactions between ethanol and adenosine agonists and antagonists in the striatum were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In humans, the nonselective adenosine receptor antagonist caffeine reduces sleepiness and psychomotor performance impairment produced by moderate-to-high ethanol doses (Franks et al, 1975;Fillmore and Vogel-Sprott, 1995;Liguori and Robinson, 2001;Drake et al, 2003). In rodents, adenosine receptors seem to modulate some of the pharmacological properties of ethanol, such as sedative/ hypnotic effects (El Yacoubi et al, 2003), motor incoordination (Meng and Dar, 1995;Barwick and Dar, 1998;Dar, 2001), and development of rapid tolerance to ethanolinduced motor impairments (Batista et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the nonselective adenosine receptor antagonist caffeine reduces sleepiness and psychomotor performance impairment produced by moderate-to-high ethanol doses (Franks et al, 1975;Fillmore and Vogel-Sprott, 1995;Liguori and Robinson, 2001;Drake et al, 2003). In rodents, adenosine receptors seem to modulate some of the pharmacological properties of ethanol, such as sedative/ hypnotic effects (El Yacoubi et al, 2003), motor incoordination (Meng and Dar, 1995;Barwick and Dar, 1998;Dar, 2001), and development of rapid tolerance to ethanolinduced motor impairments (Batista et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the combined administration of caffeine and alcohol can increase the development of alcohol tolerance (Fillmore, 2003). In rodents, many studies using selective adenosine receptor agonists and antagonists have consistently demonstrated that adenosine receptors, localized in brain areas essential for motor control such as striatum, the cerebellum, and the motor cortex, are the primary site where adenosine modulates the incoordination induced by ethanol (Meng and Dar, 1995;Barwick and Dar, 1998;Dar, 2001). Additionally, we have recently demonstrated that the blockade of adenosine receptors inhibits the development of rapid tolerance to ethanol-induced motor impairment in mice (Batista et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Striatal A2AR signaling Striatal adenosine levels play an important role in ethanol sensitivity, withdrawal, and drinking (Arolfo et al, 2004;Gordon and Diamond, 1993;Meng and Dar, 1995;Nagy and DeSilva, 1994). The A2AR is enriched in the striatum and exclusively expressed in striatopallidal neurons, while A1Rs are widely distributed throughout the CNS.…”
Section: Adenosine Receptor Signaling In Ethanol Drinkingmentioning
confidence: 99%
“…It was found that the use of adenosine agonists accentuate the reduction in the motor coordination induced by ethanol, whereas Ro15-4513, a weak partial inverse agonist of the benzodiazepine class of drugs, attenuated by blocking the effect of the first when used in combination Dar, 1994Dar, , 1995, suggesting a participation via GABA A by an alteration in the conductance of chloride ions (Meng et al, 1997, Mohler et al, 1984. A mechanism suggested by Londos et al (1980) and Van Calk et al (1970) relates ethanol to alterations in the production of cAMP via AC through the A1 receptor, ie, increased availability of adenosine induced by ethanol leads to greater signs of adenosine on your receptor that has a higher affinity, which is related with inhibitory G protein, reducing cAMP production and concomitant modulation of the GABAergic system that increases chloride conductance.…”
Section: Ethanol and Adenosine Relation In Different Neurotransmissiomentioning
confidence: 99%
“…The GABAergic system in the striatum may be modulated by adenosine with regard to the effects of ethanol on motor coordination and sleep, involving cAMP Dar, 1995;Meng et al, 1997). It was found that the use of adenosine agonists accentuate the reduction in the motor coordination induced by ethanol, whereas Ro15-4513, a weak partial inverse agonist of the benzodiazepine class of drugs, attenuated by blocking the effect of the first when used in combination Dar, 1994Dar, , 1995, suggesting a participation via GABA A by an alteration in the conductance of chloride ions (Meng et al, 1997, Mohler et al, 1984.…”
Section: Ethanol and Adenosine Relation In Different Neurotransmissiomentioning
confidence: 99%